1H HR-MAS NMR spectroscopy as a simple tool to characterize peptide – Functionalized hydrogels as a function of cross linker density. (15th January 2015) - Sallouh, Muhammad; Degen, Patrick; Hiller, Wolf; Weberskirch, Ralf
Abstract: High resolution magic angle spinning ( 1 H HR-MAS) NMR spectroscopy has been used to analyze the composition of a set of bioactive hydrogels. Therefore, a set of six hydrogels with different cross linker densities ranging from 1 to 12 mol% were prepared by free radical polymerization. The disulfide based cross linkers of the hydrogels were reduced with dithiothreitol (DTT) to generate free sulfhydryl groups giving access to soluble copolymers. Comparison of the 1 H NMR results of the soluble copolymers with those obtained from 1 H HR-MAS experiments revealed that for lower cross linker densities of 1–2 mol%, HR-MAS spectroscopy of the hydrogels matches quantitatively the peptide content of the soluble copolymer. With increasing cross linker densities up to 12 mol% the signal intensity of the aromatic unit is linearly reduced to 62% compared to the results obtained by 1 H NMR spectroscopy. Graphical abstract: Highlights: 1 H HR-MAS NMR spectroscopy was used to characterize the composition of hydrogels as a function of cross linker densities. 1 H HR-MAS NMR spectroscopy is a simple tool to quantify bioactive peptide content in cross linked gels. NMR results of 1 H HR-MAS NMR and 1 H NMR spectroscopy are in good agreement for low cross linker densities.